Respuesta :

Answer:

[tex]y = -\frac{2}{3}x + 5[/tex]

Step-by-step explanation:

First you have to find the slope

[tex]m = \frac{7 - 3}{-3 - 3} = \frac{4}{-6} = -\frac{2}{3}[/tex]

Now use the point-slope form by using one of the points and the slope.  Let's use the point (3, 3)

[tex]y - 3 = -\frac{2}{3} (x - 3)[/tex]

Multiply thru the equation by 3 to remove the fraction

3y - 9 = -2(x - 3) =

3y - 9 = -2x +6

3y = -2x + 15

[tex]y = -\frac{2}{3}x + 5[/tex] is the equation in slope-intercept form

ACCESS MORE